Design and implementation of a QPSK demodulator - Hasan, Mahabubul; Akhter, Farzana (BRAC University, 2011)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2010.